Functional law of the iterated logarithm for fields and its applications - Bondarev, B. V.; Zhirnyi, G. G. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
For a Wiener field with an arbitrary finite number of parameters, we construct the law of the iterated logarithm in the functional form. We consider the problem for random fields of a certain type to reside within curvilinear boundaries without assuming that the Cairoli—Walsh condition is satisfied.